2019
DOI: 10.1001/jamanetworkopen.2019.8427
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiparametric Magnetic Resonance Imaging and Targeted Biopsy With Systematic Biopsy Alone for the Diagnosis of Prostate Cancer

Abstract: Key Points Question Is prebiopsy magnetic resonance imaging combined with targeted biopsy associated with improved detection of clinically significant prostate cancer compared with transrectal ultrasonography–guided systematic prostate biopsy alone? Findings This systematic review and meta-analysis of 7 randomized clinical trials (2582 patients) demonstrates that prebiopsy magnetic resonance imaging combined with targeted biopsy is associated with improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 40 publications
0
41
0
3
Order By: Relevance
“…Many studies have shown that the utility of FBx is in the combination of SBx and MRI-targeted cores, [3][4][5][6][7][8] although some studies argue that MRI-targeted cores alone would significantly reduce insignificant cancer diagnosis. 9 In contrast to the multitude of studies on the possible efficacy of MRItargeted biopsy alone in FBx, to our knowledge, there has not been a study that looked solely at utilization of the machineguided SBx of an FBx captured by a software-assisted (fusion) registration device. We sought to compare the CS CDRs of machine-guided SBx with the standard, freehand TRUS-SBx in hopes of identifying a newfound usage for softwareassisted (fusion) registration devices in the detection of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the utility of FBx is in the combination of SBx and MRI-targeted cores, [3][4][5][6][7][8] although some studies argue that MRI-targeted cores alone would significantly reduce insignificant cancer diagnosis. 9 In contrast to the multitude of studies on the possible efficacy of MRItargeted biopsy alone in FBx, to our knowledge, there has not been a study that looked solely at utilization of the machineguided SBx of an FBx captured by a software-assisted (fusion) registration device. We sought to compare the CS CDRs of machine-guided SBx with the standard, freehand TRUS-SBx in hopes of identifying a newfound usage for softwareassisted (fusion) registration devices in the detection of PCa.…”
Section: Discussionmentioning
confidence: 99%
“… Elwenspoek et al. [ 35 ] - Systematic review and meta-analysis - Evaluated three biopsy Pathway systematic biopsy MRI-TB Both pathway - 7 RCTs (2 582 men) csPca definition varied in different series - 57% improvement in detection of csPca, 33% reduction in number of biopsy and 77% reduction in the number of cores. Woo et al [ 36 ] - Systematic reviews and meta-analysis MRI-TB MRI plus systematic biopsy as intervention Systemic TRUS as comparator - 9 RCTs (2 908 men) csPca definition varied in different series - MRI stratified pathway detected more clinically significant PCa than TRUS biopsy (relative detection rate 1.45 for all men, 1.42 for biopsy naïve and 1.6 for men with prior negative biopsy).…”
Section: Mri-tbmentioning
confidence: 99%
“…The article by Elwenspoek et al 7 summarizes the findings of 7 randomized clinical trials evaluating whether the traditional technique of obtaining 10 to 12 biopsy cores distributed within the prostate is superior to a technique that biopsies only lesions seen at MRI. The clinical trials differed in many respects, but the overarching conclusion is that targeted biopsies appear to be much better at identifying clinically significant disease while avoiding clinically insignificant disease than techniques that sample the entire prostate.…”
Section: Scandinavian Prostate Cancer Group 4 Trial and The Goteborgmentioning
confidence: 99%